The Effect of Learning by Using The Learning Media in Islamic Religious Education in Muhammadiyah High School 9 Sedayulawas Brondong Lamongan - Rejo no; Rahmat Arofah Hari Cahyadi (Studia Religia : Jurnal Pemikiran dan Pendidikan Islam, 2019)
The purpose of this study was to discuss how the influence of media use on the learning of Islamic Education in Muhammadiyah High School 9 Sedayulawas Brondong Lamongan, how to constrain the use of media, and how to overcome these obstacles. This type of research uses research with a qualitative approach, while this study uses data collection techniques with Observation, Interview and Documentation. While processing and analyzing data using data obtained from observations, interviews, written footage from documentaries, field notes, is not stated in statistical numbers. The research findings in this study can be concluded: First: Based on the results of research that has been done shows that using the learning media LKS and LCD Projectors can increase student motivation in learning Islamic Religious Education at Muhammadiyah High School 9 Sedayulawas Brondong Lamongan. Second: The constraints that researchers found when using the media LKS and LCD Projectors in learning Islamic Education in Muhammadiyah High School 9 Sedayulawas Brondong Lamongan as follows: Lack of students ready to follow the lessons at the first meeting using the media LKS, There are still students who forget to bring LKS. Third: The efforts made as follows: Motivating students to always be enthusiastic in following the teaching and learning process, Suggesting students to always bring His Worksheet and do not forget. Keywords: Media, Learning, PAI